HOW CARBON MARKET COOPERATION CHANGES the ENERGY SYSTEMS in NORTHEAST ASIA - Baek, Minho; Chai, Qimin; Kim, Suduk (Climate Change Economics, 2020)
This paper explores the impact of international emissions trading (IET) among Korea, China, and Japan, three countries that would form the largest potential carbon market in the world. The Nationally Determined Contribution for each country forms the basis of scenario analyses using GCAM (Global Change Assessment Model). As expected, China emerges as the sole net seller of emissions permits while Korea and Japan are the net purchasers of emission permits produced by China. All participants enjoy gains from emissions trading. The implementation of IET changes the power systems of Korea and Japan by favoring increased conventional fossil fuel usage over renewable power technologies or attached carbon capture and storage (CCS) technologies, while China's power system moves in the opposite direction, by boosting the deployment of renewables and CCS-attached technologies. Considering the counterproductive incentives for Korea and Japan to consume more carbon-intensive energy sources, each country should consider such issues carefully before officially adopting IET as the pillar of climate policy.
Keywords: China; global change assessment model; international emissions trading; Japan; Korea; nationally determined contribution